Prognostic importance of prostate specific antigen in assessing histological grade of prostatic adenocarcinoma - Shanthi Vissa; Venkata Vydehi Bheemaraju; Bhavana Grandhi; Swathi Sreesailam; Shehnawaz Bhat; Dahlia Joseph (International Journal of Medical Research and Review, 2015)
Background: Prostatic adenocarcinoma is one of the most common cancer occurring in the men above 50 years of age. Prostate specific antigen (PSA) is an important serum marker which helps in the diagnosis of prostatic adenocarcinoma and also aids in estimating the tumor grade.Objective: To evaluate the correlation between serum PSA levels and Gleason’s histological grade of prostatic adenocarcinoma.Methods: A retrospective study analysis was done for 128 patients whose transrectal ultrasonography (TRUS) guided prostate biopsy were studied in our hospital. The serum PSA levels were noted and compared with different Gleason histological grading in adenocarcinoma patients.Results: Our study included 128 cases, out of which 86 cases were benign and 42 cases were malignant. Maximum numbers of benign and malignant lesions were in the age group of 60 – 69 years. Most of the malignant cases (80.95%) had PSA level above 20ng/ml. Histological grade III carcinomas were restricted to PSA levels of 50ng/ml and above, while grade I was restricted to PSA level of less than 10ng/ml and grade II carcinomas did not have any correlation with specific PSA levels.Conclusion: Our study showed that there was significant correlation between serum PSA value and Gleasons histological grade of prostatic adenocarcinoma.